Governance attributes in Indonesia and earnings quality - Rusmin, Rusmin; Hossain, Mahmud; Evans, John (Virtus Interpress, 2011)
This research investigates the relationship between corporate governance structure and attributes and the quality of reported earnings in a sample of Indonesian firms. The findings of our research reveals that both concentrated and family ownership are associated with lower earnings quality. In addition we find that independent members of a board committee act as an effective monitoring mechanism to oversee the accounting and financial reports processes of a company.